ОКРЕМІ ПИТАННЯ ПОДІЛУ АДМІНІСТРАТИВНОГО ПРОЦЕСУ ТА ВИЗНАЧЕННЯ МІСЦЯ ВИКОНАВЧОГО ПРОЦЕСУ - Міхеєв, М.В. (SUPREMANCE OF LAW, 2018)
The article deals with the question of the division of the administrative process into conflict and nonconflict. In addition, the place of the executive process is determined. It is proved that the executive process is not in itself conflict, but conflicts may arise as a result of its implementation, and thus it may cause a conflict. It is proposed to determine the executive process as having a double orientation.
Keywords: administrative process; administrative proceeding; executive process; enforcement proceedings; confl ict proceedings; non-confl ict proceedings